Silicon nanowire characterization for fatigue and reliability - Yim, Wai Tat. (2011)
This final year project report mainly focus on a project that is in conjunction with A*STAR Institute of Microelectronics in performing a study on the silicon nanowire characterization for fatigue and reliability.